From school to the farm: an assessment of the motivation to become agropreneurs among students in Lagos owned tertiary institutions - Azeez Rasheed O. (2023)
In spite of the strategic importance of agriculture to the development of nations, agricultural-based entrepreneurship (agropreneurship) seems to be an unfavoured option among youths schooling – and living- in urban settlements such as Lagos state, Nigeria. Despite the various agropreneurship initiatives being implemented by the Lagos State Government through its agencies and institutions, the youth or young entrepreneurs desire to pursue their careers in the service, technology, fashion and entertainment sectors where it is happening and trendy. Consequently, the push to become agropreneurs seems to be somewhat restricted to undergraduate students motivated by factors unknown to many researchers and policy makers. This study assessed the factors that motivate Lagos-owned tertiary institutions’ undergraduate students to become agropreneurs. Using the concurrent transformative mixed method research design, data were collected from young agropreneurs (campus farmers) who are undergraduates of the three tertiary institutions – Lagos State University (LASU), Lagos State University of Education (LASUED), Lagos State University of Science and Technology (LASUSTECH) – owned by Lagos State using the interview and questionnaire methods. Respondents were asked about their motivations to start a business in the agriculture sector, and results of the analysis using simple percentage and content analysis brought to the fore that, among the key motivators for the respondents to start their agro-based businesses were to challenge themselves to think out of the box, becoming independent with the ability to control their time, pursuing their dream, elevating their socio-economic status, and to solve the food crisis. Based on the results, this study recommended amongst others that, government through its specialized ministries, departments and agencies should create policies that encourages campus farming project and also, grants should be made available to campus farmers based on the quantity of their produce yearly.